(untitled) - Hewlett, Sylvia Ann (Massachusetts, 2011)
Drawing on groundbreaking research, amplified with on-the-ground examples from companies as diverse as Google, Infosys, Goldman Sachs, and Siemens, this book is required reading for all companies seeking to strengthen their talent pipeline in these rich and expanding markets.
Keywords: Phụ nữ trong các ngành nghề,Women in the professions